Analisis determinan ekspor minyak mentah Indonesia - Nurjanah, Rahma; Bhakti, Adi (Jurnal Paradigma Ekonomika, 2020)
The objectives of this study are to analyze the development of exchange rates, labor in the mining sector, and economic growth and the volume of Indonesia's crude oil exports abroad from 1995 to 2017. To analyze the effect of the exchange rate, mining sector labor, and economic growth on oil export volumes Indonesian crude oil abroad during 1995 to 2017 The development of Indonesia's crude oil export volume, the exchange rate, the mining sector labor, and Indonesia's economic growth conditions during the period 1995 to 2017 fluctuated or fluctuated, with the average volume of crude oil exports growing at -1.59%, and the exchange rate was 14.17%, economic growth was 4.48%, and the mining sector workforce was 4.80%. Regression results show that of the three determinants that affect crude oil exports, namely the exchange rate, economic growth, and labor in the mining sector all have a significant negative effect on Indonesia's crude oil export volume.